Sleep problems in community-dwelling postmenopausal and older women in India: a country level cross-sectional analysis - Vansh Maheshwari; Suruchi Mishra; Saurav Basu (Discover Public Health)
Abstract Objectives Menopause is characterized by onset of sleep problems among women due to altered hormonal profile. This study aimed to investigate the prevalence and determinants of sleep problems in postmenopausal women in India, utilizing nationally representative data. Study design This cross-sectional study utilized secondary data from the Longitudinal Aging Study in India (Wave 1: 2017–2018). Main outcome measures Sleep problems were assessed using five modified Jenkins Sleep Scale questions, with ‘frequently’ indicating sleep problems, and a cumulative score (5 to 20) measuring overall sleep quality. Results The study included 28,160 postmenopausal women aged ≥ 50 years. The weighted prevalence of sleep problems among the participants was 22.27% (95% CI: 21.41, 23.16). Adjusted analyses revealed that higher education (aOR = 0.56, 95% CI: 0.39, 0.79) and physical activity (aOR = 0.65, 95% CI: 0.51, 0.82) were associated with lower odds of sleep problems. Conversely, lower socioeconomic status (poorer wealth quintile) (aOR = 1.38, 95% CI: 1.03, 1.85), having one morbidity (aOR = 1.46, 95% CI: 1.18, 1.79), and having ≥two morbidities (aOR = 1.50, 95% CI: 1.17, 1.93) increased the odds of sleep problems. Additionally, better sleep quality scores were associated with higher education levels, urban residence, and physical activity, while poorer scores were linked to tobacco use and higher morbidity. Conclusions Over one-fifth of postmenopausal women in India experience sleep problems, significantly linked to modifiable risk factors such as education, physical activity, and chronic morbidities. Preventative population health strategies should consider enhancing physical activity, improving educational opportunities for sleep hygiene, and promoting tobacco cessation. Highlights 22.27% of postmenopausal women in India report frequent sleep problems. Lower socioeconomic status and multiple morbidities associated with sleep problems. Improved sleep quality is associated with higher education, urban residence, and physical activity.